One‐Pot Three‐Component Synthesis of Benzo[f]thiopyrano[3, 4‐b]quinolin‐11(8H)‐one Derivatives. (3rd December 2013) - Yu, Chenxia; Zhang, Honghong; Yao, Changsheng; Li, Tuanjie; Qin, Bingbin; Lu, Jun; Wang, Donglin
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>